Hubungan karakteristik rumah tangga dengan penggunaan ruang jalan di perumahan menengah - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Psikologi Universitas Gadjah Mada, 1998)
ABSTRACT The need of housing in urban area steeply increases a line conjunction with the high population growth. In contrast, the limited availability of land creates excessive increase in land price. Such conditions lead to limiting people capabilities in having proper houses. Many residential areas with small land areas seem to be unable to accommodate their daily activities in the housing area. Those spilling activities will affect to road space and create impedance to traffic, as well as to environment comfort and safety. Based on three locations of the middle class residential area, those are : Mataram Bumi Sejahtera, Puri Gejayan Indah and Tiara Grand Estate, some supporting factors in the use of road space for non traffic activities can be achieved, such as : the building size, the size of remaining area, the income, the family size, the number of children and teenagers, and the number of private car. Further more the supporting factors are analyzed using cross tab analysis to observe their correlation to the use of road space. The result shows that there is strong correlation between the use of road space and the remaining area, the income, and the number of children and teenagers.